Analisis Kinerja Pegawai Berdasarkan Gaya Kepemimpinan, Motivasi Kerja dan Disiplin Kerja dengan Komitmen Organisasi Sebagai Variabel Intervening pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Sungai Penuh - Pratama, Rizky Aditya; Yulasmi, Yulasmi; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the extent of employee performance analysis based on leadership style, work motivation, and work discipline with organizational commitment as an intervening variable at the body of civil service and human resource development in Sungai Penuh City. The data collection method used surveys and distributing questionnaires, with a sample of 77 respondents. The analysis method used is structural equation modeling using SmartPLS. The research results show a significant influence of leadership style on organizational commitment at the Personnel and Human Resource Development Agency of Sungai Penuh City. There is a significant influence of work motivation on organizational commitment. There is a significant influence of work discipline on organizational commitment. There is an insignificant influence of leadership style on employee performance. There is an insignificant influence of work motivation on employee performance. There is an insignificant influence of work discipline on employee performance. There is a significant influence of organizational commitment on employee performance. Organizational commitment mediates the influence of leadership style on employee performance. Organizational commitment mediates the influence of work motivation on employee performance. Organizational commitment does not mediate the influence of work discipline on employee performance at the Personnel and Human Resource Development Agency of Sungai Penuh City.